Predictors of Early Postoperative Complications after Modified Radical Mastectomy: A Prospective Study of 105 Patients - Muhammad Nadeem, Muhammad Usman Aslam, Raza Akram, Tanvir Ahmad Bhatti, Zahid Saeed, Shamaila Ayub (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Modified radical mastectomy (MRM) with level II axillary clearance is still widely performed in breast cancer management, particularly in low- and middle-income countries. However, postoperative complications remain a concern. Objective: To evaluate the frequency, risk factors, and predictors of early complications in patients undergoing MRM with level II axillary clearance. Methods: A prospective observational study was conducted on 105 female patients with operable breast carcinoma undergoing MRM with level II axillary clearance. Demographic and surgical variables were recorded. Patients were followed for 30 days to document complications. Logistic regression analysis was performed to identify predictors of complications. Results: The mean age of patients was 52.6 ± 9.1 years. Seroma was the most common complication (32.4%), followed by sensory loss (38.1%), wound infection (17.1%), hematoma (8.6%), flap necrosis (6.7%), and wound dehiscence (4.8%). Logistic regression identified obesity (OR: 2.8; 95% CI: 1.3–6.4; p=0.01), diabetes mellitus (OR: 2.5; 95% CI: 1.1–5.9; p=0.04), and operative time >120 minutes (OR: 3.2; 95% CI: 1.4–7.3; p=0.006) as independent predictors of major complications. Conclusion: Early complications after MRM with level II axillary clearance are common, with seroma and sensory loss most frequent. Obesity, diabetes, and prolonged operative time significantly increase the risk. Preventive strategies targeting these factors may reduce morbidity. Keywords: Modified radical mastectomy; axillary clearance; complications; seroma; logistic regression